BPM theory for laymen theory matters! the scenic tour of the Pi Calculus and Petri nets for BPM and choreography practitioners. - Havey, Michael (SOA webservices journal.)
In most software topics, the boundary between theory and practice in software is clearly demarcated : theory is for academics who seldom descend from the ivory tower, practice is for industry professionals who have long forgotten the concepts and application of theory. In concurrency, for example, most developers either know or have programmed semaphores, but few remember the conceptual underpinnings devised by Dijkstra. But Business Process Management (BPM)- a key Web services technology with close ties to Web services choreography-belongs to a rarer category, in which theory informs practical design and theoretical jargon is part of the hype with customers.